Proceedings of the National Scientific Students' Conference "Chemistry and Chemical Technology 2019" - Tumkevičius, Sigitas; Inkrataitė, Greta; Daumantas, Liudas (Vilnius University Proceedings, 2019)
Scientific Committee:Prof. A. Beganskienė, VUDoc./Assoc. Prof. J. Dodonova, VUProf. V. Getautis, KTUProf. S. Grigalevičius, KTUDoc./Assoc. Prof. T. Paulauskienė, KUProf. S. Tumkevičius, VUProf. A. Žukauskaitė, KU Organizers:Prof. S. Tumkevičius (Chairman), VUG. Inkrataitė (secretary), VUDr. R. Vaitkus, VUDr. S. Višniakova, VUI. Gabriūnaitė, VUL. Sinušaitė, VUM. Steponavičiūtė, VUM. Vagner, VUO. Safinas, VU SAL. Daumantas, VU
Keywords: Analytical and Environmental Chemistry; Biochemistry, Biotechnology and Bioengineering; Pharmaceutical Chemistry and Technology; Physical Chemistry; Functional Organic and Inorganic Materials; Production Waste Utilization; Geochemistry; Nanomaterials Chemistry and Technology; Inorganic Chemistry and Technology; Oil Chemistry and Technology; Organic Chemistry; Polymer Chemistry and Technology